THE ROLE OF ENDOCRINOLOGY IN THE TREATMENT OF MULTIFOLLICULAR OVARIAN CYSTS - Qosimova Mohlaroyim Bahromjon kizi; Khodjayeva Dilnoza Bobirjon kizi (TADQIQOTLAR, 2026)
Abstract: This article highlights the pivotal role of endocrinology in the treatment of multifollicular ovarian cysts. The research delves into the pathophysiological mechanisms behind multifollicular ovarian changes, discussing the influence of hormonal imbalances and endocrine disorders on ovarian function. The article further analyzes various therapeutic approaches from an endocrinological perspective and evaluates their effectiveness, emphasizing the necessity of integrative and individualized treatment strategies. The importance of early diagnosis, comprehensive hormonal assessment, and collaboration between gynecologists and endocrinologists are also discussed. Key recommendations for advancing clinical practice in managing multifollicular ovarian cysts are provided.